Face Recall and Face Recognition: Description Accuracy Does Not Indicate Eyewitness Identification Accuracy - Fazlic, Adnan; Deljkić, Irma (NBP. Nauka, bezbednosti, policija, 2025)
Eyewitness testimonies are frequently considered crucial in criminal investigations. The impact of the initial description provided by an eyewitness on subsequent identification accuracy remains an understudied area. We employed a slightly modified version of Schooler and Engstler-Schooler’s (1990) experimental approach to assess whether description quantity and quality are related to lineup identification accuracy. The sample comprised 99 undergraduate students from the University of Sarajevo. More than 50% of our participants made an accurate lineup identification, whereas they recalled and described only the general physical characteristics with minimal detail. No significant relationship between the quantity/quality of descriptions and identification accuracy was observed in terms of the total number of words, total number of details in the description, and individual characteristics that participants mentioned in the description. In other words, neither an extensive nor a detailed description effectively predicts lineup identification accuracy. Finally, our findings suggest that the recognition task is significantly less challenging for participants than the recall and description tasks because descriptions provide a general impression of an individual and lack detailed information. These results were considered within cultural, generational, and practical contexts.